Distribution and role of fluorine in the aquatic ecosystem (mineral springs, groundwater, tributaries, Baikal water, and the Angara water source) of Lake Baikal, Russia - Valentina Grebenshchikova; Mikhail Kuzmin; Anna Novopashina; Elena Kuz'mina (China Geology)
ABSTRACT: Several conjugate components represent the aquatic ecosystem of Lake Baikal: Baikal water (surface and deep water), groundwater from boreholes, water of numerous Baikal tributaries, cold and hot mineral springs around Lake Baikal, and the Angara River, the only runoff reflecting all this aquatic diversity. River waters in the Baikal region are known to be deficient in some vital elements, including fluorine. This article discusses the features of the fluorine distribution in the water from the conjugate components of the Baikal ecosystem. Fluorine ion concentrations in the water of the Baikal ecosystem was determined using the potentiometric method. The study represents the monitoring that was carried out between 1997 and 2022 years. We determine likely causes of high and low fluorine concentrations in the water from different components, propose and substantiate the fluorine sources, geological and geochemical model of its influx and distribution features in the water of the Baikal ecosystem.